Adamystis thailandensis sp. nov. (Acari: Prostigmata: Adamystidae), a new species of soil mites from Thailand with a key to world species of Adamystidae - Fuangarworn, Marut; Lekprayoon, Chariya (Zootaxa, 2010)
A new species of soil prostigmatic mites, Adamystis thailandensis sp. nov. (Acari: Adamystidae) is described based on adult and immature specimens collected from leaf litter and upper soil layer in a coastal forest in southern Thailand. It differs from its congeners by the presence of a densely striated idiosomal shield and the presence of lens-like structures on the lateral, posterior dorsomedial, and ventral sides of the idiosoma. A diagnostic key to the known species of Adamystidae is presented.